Partial characterization of an enzymatic extract from Bentong ginger (Zingiber officinale var. Bentong) - Nafi', Ahmad; Foo, Hooi Ling; Bakar, Jamilah; Mohd Ghazali, Hasanah (MDPI, 2014)
Extraction of protease from a local ginger rhizome (Zingiber officinale var. Bentong) was carried out. The effect of extraction pH (6.4, 6.8, 7.0, 7.2, 7.6, 8.0, 8.4, and 8.8) and stabilizers (0.2% ascorbic acid, 0.2% ascorbic acid and 5 mM EDTA, or 10 mM cysteine and 5 mM EDTA) on protease activity during extraction was examined. pH 7.0 potassium phosphate buffer and 10 mM cysteine in combination with 5 mM EDTA as stabilizer were found to be the most effective conditions. The extraction procedure yielded 0.73% of Bentong ginger protease (BGP) with a specific activity of 24.8±0.2 U/mg protein. Inhibitory tests with some protease inhibitors classified the enzyme as a cysteine protease. The protease showed optimum activity at 60 °C and pH 6-8, respectively. The enzyme was completely inhibited by heavy metal cations such as Cu2+, and Hg2+. SDS stimulated the activity of enzyme, while emulsifiers (Tween 80 and Tween 20) slightly reduced its activity. The kinetic analysis showed that the protease has Km and Vmax values of 0.21 mg mL-1 and 34.48 mg mL-1 min-1, respectively. The dried enzyme retained its activity for 22 months when stored at -20 °C.